2018
DOI: 10.1016/j.bpsc.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Variants of Psychopathy in a Volunteer Sample Are Associated With Different Neurocognitive Mechanisms

Abstract: Distinct neural correlates of fear processing characterize individuals with primary and secondary psychopathy. The reduced neural response to fear that characterizes individuals with the primary variant of psychopathic traits is not observed in individuals with the secondary presentation. The neurocognitive mechanisms underpinning secondary psychopathy warrant further systematic investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 64 publications
1
29
0
2
Order By: Relevance
“…Note that our results are still consistent with other research pointing out that adult Secondary psychopathy is related to average levels of autonomic responsivity in anticipation of aversive outcomes (Lykken, ), and that youth in the Secondary group show normative physiological responding to negative stimuli (Dackis et al ., ). Our findings also agree with a recent fMRI study providing evidence that the Secondary group showed similar amygdala activity in response to fearful facial expressions (signalling the presence of a threat) as the comparison group (Sethi et al ., ). Interestingly, this group also showed a relative hyper‐responsivity to the CS+ during threat extinction, which would be in agreement with the notion that the threat circuit is hyper‐active in Secondary psychopathy.…”
Section: Discussionmentioning
confidence: 97%
“…Note that our results are still consistent with other research pointing out that adult Secondary psychopathy is related to average levels of autonomic responsivity in anticipation of aversive outcomes (Lykken, ), and that youth in the Secondary group show normative physiological responding to negative stimuli (Dackis et al ., ). Our findings also agree with a recent fMRI study providing evidence that the Secondary group showed similar amygdala activity in response to fearful facial expressions (signalling the presence of a threat) as the comparison group (Sethi et al ., ). Interestingly, this group also showed a relative hyper‐responsivity to the CS+ during threat extinction, which would be in agreement with the notion that the threat circuit is hyper‐active in Secondary psychopathy.…”
Section: Discussionmentioning
confidence: 97%
“…CU traits seem typically associated with reduced anxiety (Frick et al , 2013; Eisenbarth et al , 2016). Cases with CU traits and co-occurring high levels of anxiety might represent a distinct phenotype with different clinical outcomes (Fanti, Demetriou and Kimonis, 2013) and neural correlates (Sethi et al , 2018). To conclude, our results emphasize to differentiate between aggression subtypes and consider comorbid anxiety and ADHD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Self-report measures allow researchers to screen a large pool of participants from community samples and individuals scoring highly on the trait of interest can then be recruited for further research [76]. Similar to Sethi et al [33], a quartile split approach was used in the current study. While only 50 participants completed the eye-tracking task, the screening process allowed us to identify participants that varied considerably in their Levenson SRPS and AAS scores.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Primary psychopathy is thought to have a significant genetic component and is associated with planned, deliberate action and a lack of emotional responses [30][31][32]. On the other hand, Secondary psychopathy is thought to be a consequence of environmental factors such as a history of maltreatment, and is characterised by deficits in impulse control [31][32][33]. Importantly, in contrast to Primary psychopathy, Secondary psychopaths are thought to have the ability to feel remorse and fearfulness [34].…”
Section: Introductionmentioning
confidence: 99%